[Article Retracted] PENGEMBANGAN SISTEM DAN PELAKSANAAN TRACER STUDY ALUMNI IAIN PURWOKERTO TAHUN 2014-2016 - Suwito N.S; H.M. Slamet Yahya; Arif Hidayat (Jurnal Penelitian Agama, 2017)
This article is retracted, because it has been published in Jurnal Manajemen Pendidikan volume 2 number 3 of 2017. To read the full text of this article please visit https://ejurnal.stkip-pessel.ac.id/index.php/jmp/article/view/182/0 with a DOI number http://dx.doi.org/10.34125/mp.v2i3.182. Thus the statement of retraction is made to make sense of it. Abstract: This paper aims to reveal the relevance (suitability) of graduate education is indicated by job profile (type and place of work), the relevance of work with educational background, benefits of courses programmed in work, advice from graduates to improve graduate competency. In addition, the relevance of education is also shown through the opinions of graduate users about graduate user satisfaction, graduate competency and graduate advice to improve graduate competency. As a result, the suitability of the work with the expectation when studying is also a problem of job satisfaction, some feel that they are satisfied with the work that is now being undertaken. The main consideration of alumni in working is not solely because of salary factors is an interesting finding from this study. This can be seen in graduates who are teachers (education sector) with salaries that are still minimal but in accordance with the scientific field. In general, alumni income ranges from one million to three million per month. This is because they work following the district/city minimum wage (UMK) which ranges from Rp. 1,000,000 - Rp. 3,000,000, although many are still under one million rupiah. Some alumni have worked before graduation, although in general, the alumni of 2014-2016 IAIN Purwokerto worked with a waiting period of 3 months. They are mostly in the education sector. Keywords: Alumni, Employment, Users, IAIN Purwokerto, Education